World War 1 education kit - Townsville (Qld.). Council; Townsville City Libraries (Townsville, Queensland : Townsville City Council, 2015)
The World War 1 Education Kit has two aims, first to illustrate the relevance of CityLibraries Townsville's Local History Collection to the Australian History Curriculum and second to assist teachers in creating a meaningful and interesting history unit relevant to Anzac Day.
Title from PDF cover page.
Keywords: Townsville (Qld.). -- Council; Anzac Day -- Study and teaching; World War, 1914-1918 -- Study and teaching